Do others’ health count for peanuts? Health, market returns, and pro-sociality - Abate, Gashaw T.; Bernard, Tanguy; Deutschmann, Joshua; Fall, Fatou (International Food Policy Research Institute, 2025)
Individuals often make decisions considering both private returns and welfare impacts on others. Food safety decisions by smallholder agricultural producers exemplify this choice, particularly in low-income countries where farmers often consume some of the food crops they produce and sell or donate the rest. We conduct a lab-in-the-field experiment with peanuts producers in Senegal to study the decision to invest in food safety information, exogenously varying the degree of private returns (monetary or health-wise) and welfare impacts on others. Producers are willing to pay real money for food safety information even absent the potential for private returns, but willingness to pay increases with the potential for private returns. A randomized information treatment significantly increases willingness to pay in all scenarios. Our results shed light on the complex interplay between altruism and economic decisions in the presence of externalities, and point to the potential of timely and targeted information to address food safety issues.